The Upper Campanian - lower Maastrichtian cephalopod fauna of Botellos, Nuevo León: a key to understand faunal turnover across the Campanian-Maastrichtian boundary in NE Mexico - Ifrim, Christina; Cerda, Jacobo Edgar Lara de la; Stinnesbeck, Wolfgang (Acta geologica Polonica, 2017)
A new cephalopod collection from the Campanian-Maastrichtian boundary interval of NE Mexico, consisting of 1076 individuals assigned to 29 species and 22 genera is presented. This collection is a mix of ammonoids, one coleoid and one nautilid, which originate from at least three ammonoid biozones: The upper Campanian Exiteloceras jenneyi and Nostoceras (Nostoceras) hyatti zones, and the lower Maastrichtian Pachydiscus (Pachydiscus) neubergicus Zone. The age of the collection is thus middle late Campanian to late early Maastrichtian, and it closes a stratigraphic gap between faunas described formerly from this region. The specimens are nuclei collected from the desert pavement. The abundance of specimens allows for a comparison to other Campanian-Maastrichtian ammonoid records from Mexico, North America and Europe.